A Complex Relationship between TRAF3 and Non-Canonical NF-κB2 Activation in B Lymphocytes - Lin, Wai W.; Hildebrand, Joanne M.; Bishop, Gail A. (Frontiers in Immunology, 2013)
The adaptor protein TRAF3 restrains BAFF receptor (BAFFR) and CD40-mediated activation of the NF-κB2 pathway in B cells. Mice lacking TRAF3 specifically in B cells revealed the critical role of TRAF3 in restraining homeostatic B cell survival. Furthermore, loss- of-function mutations of the traf3 gene have been associated with human B cell malignancies, especially multiple myeloma (MM). It has been proposed that receptor-induced TRAF3 degradation leads to stabilization of the NF-B inducing kinase NIK, and subsequent NF-κB2 activation. However, it is unclear how receptor-mediated TRAF3 degradation or loss of function contributes to B cell-specific NF-κB2 activation. In the current study, we employed two complementary models to address this question. One utilized a mutant traf3 gene found in a human MM-derived cell line called LP1. The LP1 mutant TRAF3 protein lacks the TRAF-N and TRAF-C domains. Consistent with the paradigm described, expression of LP1 TRAF3 in B cells promoted higher basal levels of NF-κB2 activation compared to Wt TRAF3. However, LP1 did not associate with TRAF2, CD40, or BAFFR, and no LP1 degradation was observed following receptor engagement. Interestingly, LP1 showed enhanced NIK association. Thus, TRAF3 degradation becomes dispensable to activate NF-κB2 when it is unable to associate with TRAF2. In a second model, we examined several mutant forms of BAFFR that are unable to induce NF-κB2 activation in B cells. Signaling to B cells by each of these BAFFR mutants, however, induced levels of TRAF3 degradation similar to those induced by Wt BAFFR. Thus, in B cells, receptor-mediated TRAF3 degradation is not sufficient to promote NF-B2 activation. We thus conclude that there is not a simple linear relationship in B lymphocytes between relative levels of cellular TRAF3, induced TRAF3 degradation, NIK activation and NF-B2 activation.